Enquiry into Gunpowder Weapons Used by Hülegü in the Middle East Campaign - Oğuz A.Y. (Золотоордынское обозрение)
Research objectives: To establish whether Hülegü brought gunpowder from China during his military operation in the Middle East in 1256–1260 and whether his army used gunpowder weapons against the Hashashi/Hashashin castles. Research materials: The article’s author examines Islamic and Chinese sources mentioning Hülegü’s military campaign from Mongolia to the Middle East and weapons used by the Mongolian army. Results and novelty of the research: Most researchers agree that the Mongols used gunpowder weapons adapted from the Chinese in their East Asian military expeditions, such as in China, Japan, Korea, and Java. However, it is still debated whether the Mongols used gunpowder and gunpowder weapons in their military campaigns in the West. Some researchers state that the Mongols did not use gunpowder in the European campaign and that naphtha was the main incendiary they used in the Middle East campaign. Few studies examine whether the Mongols carried gunpowder to the West. Islamic source writers described China’s novel weapons and chemicals in more familiar terms, such as naphtha. Especially when the information given by Hamdallah Mustawfi, Ata-Malik Juvayni, and Qutb al-din Shīrāzī about the Mongol Siege of Maymun-Diz in 1256 is compared with the Chinese military manual Wujing Zongyao, it is evident that the Mongols transported ballistas with three bows called “ox crossbow” from China. It turns out that these ballistas fired “rocket-assisted arrows”. These arrows carried paper tubes filled with gunpowder, which would increase their range to reach the mountain fortress of Maymun-Diz, and bombs covered with cartons, bamboo, ceramic, or metal which would set fire to the defenders of the fort. These ballistas are referred to as baban in Armenian sources and as “naphtha tools” in the Mongols’ siege of Baghdad. The most original aspect of the present article is the hypothesis that the information in Mustawfi’s work regarding the presence of “blue poison” in the arrows fired by the Mongols at the Maymun-Diz referred to black powder. “Blue poison, made up of particles”, was one of the ways by which Mustawfi expressed black powder.